A facile one-step strategy to construct 0D/2D SnO2/g-C3N4 heterojunction photocatalyst for high-efficiency hydrogen production performance from water splitting. (6th November 2020) - Wu, Huihui; Yu, Siyu; Wang, Yun; Han, Juan; Wang, Lei; Song, Ning; Dong, Hongjun; Li, Chunmei
Abstract: Fabricating 0D/2D heterojunctions is considered to be an efficient mean to improve the photocatalytic activity of g-C3 N4, whereas their applications are usually restricted by complex preparation process. Here, the 0D/2D SnO2 /g-C3 N4 heterojunction photocatalyst is prepared by a simple one-step polymerization strategy, in which SnO2 nanodots in-situ grow on the surface of g-C3 N4 nanosheets. It shows the outstanding photocatalytic H2 production activity relative to g-C3 N4 under the visible light, which is due to the formation of 0D/2D heterojunction significantly contributing to the separation of photogenerated charge carriers. In particular, the H2 production rate over the optimal SnO2 /g–C3 N4 –1 sample is 1389.2 μmol h −1 g −1, which is 6.06 times higher than that of g-C3 N4 (230.8 μmol h −1 g −1 ). Meanwhile, the AQE value of H2 production over the SnO2 /g–C3 N4 –1 sample reaches up to a maximum of 4.5% at 420 nm. This work develops a simple approach to design and fabricate g–C3 N4 –based 0D/2D heterojunctions for the high-efficiency H2 production from water splitting. Highlights: 0D/2D heterojunction was prepared by a simple one-step polymerization strategy. 0D SnO2 nanodots in situ grew on the surface of 2D g-C3 N4 nanosheets. Superior photocatalytic activity stemmed from high charge separation efficiency. H2 production rate over SnO2 /g-C3 N4 sample is 6.06 times higher than pure g-C3 N4 .